Acute aerocystitis in Nile tilapia bred in net cages and supplemented with chromium carbochelate and Saccharomyces cerevisiae - Castro, Marcello P. [UNESP]; Claudiano, Gustavo S. [UNESP]; Petrillo, Thalita R. [UNESP]; Shimada, Marina Tie [UNESP]; Belo, Marco A. A. [UNESP]; Marzocchi-Machado, Cleni M.; Moraes, Julieta R. E. [UNESP]; Wilson Manrique, G. [UNESP]; Moraes, Flavio R. [UNESP] (Elsevier B.V., 2014)
Oreochromis niloticus bred in net cages were supplemented with cell wall of Saccharomyces cerevisiae (Sc) (0.3%) or chromium carbochelate (Cr) (18 mg/kg of feed) or in association (Sc + Cr), for 90 days. After this period, acute inflammation was induced in the swim bladder by inoculation of 3 x 10(8) CFU of inactivated Streptococcus agalactiae, and another group received 0.65% saline solution (control). Twelve, 24, and 48 h after stimulation, the inflammation was evaluated through total and differential counting of accumulated cells, and through leukocyte respiratory burst in the blood, cortisolemia, glycemia and serum lysozyme concentration. The results showed that there were greater total numbers of cells in the exudate of fish inoculated with inactivated bacterium than in those injected with saline solution, with predominance of lymphocytes, thrombocytes, macrophages and granulocytes. Tilapia supplemented with Cr presented increased total numbers of cells with significant accumulation of lymphocytes and reductions in cortisolemia and glycemia, but the different treatments did not have any influence on leukocyte respiratory burst or serum lysozyme concentration. Tilapia supplemented with Sc and the Cr + Sc association did not present significant changes to the variables evaluated, despite higher accumulation of lymphocytes in the inflammatory exudate from fish treated with Sc. The results indicate that tilapia bred in net cages and supplemented with Cr presented higher total accumulation of cells at the inflammatory focus, thus indicating an increase in the inflammatory response induced by the bacterium, probably due to the reduction in cortisolemia and higher glucose consumption. Thus, supplementation with Cr had beneficial action, which facilitated development of acute inflammation induced by the bacterium, but did not affect neither leukocyte respiratory burst in the blood nor serum lysozyme concentration. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Oreochromis niloticus; Streptococcus agalactiae; Immunity; Teleost